The acute effect of flavonoid-rich apples and nitrate-rich spinach on cognitive performance and mood in healthy men and women - Bondonno, C.; Downey, L.; Croft, K.; Scholey, A.; Stough, C.; Yang, X.; Considine, M.; Ward, Natalie; Puddey, I.; Swinny, E.; Mubarak, A.; Hodgson, J. (2014)
Flavonoids and nitrate in a fruit and vegetable diet may be protective against cardiovascular disease and cognitive decline through effects on nitric oxide (NO) status. The circulating NO pool is increased via distinct pathways by dietary flavonoids and nitrate. Our aim was to investigate the acute effects of apples, rich in flavonoids, and spinach, rich in nitrate, independently and in combination on NO status, cognitive function and mood in a randomised, controlled, cross-over trial with healthy men and women (n = 30). The acute effects of four energy-matched treatments (control, apple, spinach and apple + spinach) were compared. Endpoints included plasma nitric oxide status (determined by measuring S-nitrosothiols + other nitroso species (RXNO)), plasma nitrate and nitrite, salivary nitrate and nitrite, urinary nitrate and nitrite as well as cognitive function (determined using the Cognitive Drug Research (CDR) computerized cognitive assessment battery) and mood. Relative to control, all treatments resulted in higher plasma RXNO. A significant increase in plasma nitrate and nitrite, salivary nitrate and nitrite as well as urinary nitrate and nitrite was observed with spinach and apple + spinach compared to control. No significant effect was observed on cognitive function or mood. In conclusion, flavonoid-rich apples and nitrate-rich spinach augmented NO status acutely with no concomitant improvements or deterioration in cognitive function and mood.